KINERJA USAHA AGROINDUSTRI PERABOT ROTAN DI JALAN YOS SUDARSO KECAMATAN RUMBAI KOTA PEKANBARU - Sri Puji Asweti; Jum’atri Yusri; Novia Dewi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research is: 1) identifying characteristics rattan agrobusinesses in Yos Sudarso Rumbai District of the city Pekanbaru. 2) identify agroindustry business performance wicker furniture in Yos Sudarso Rumbai District of the City. The research was do from May 2013 to June 2015. The method used was survey method using census. The results show characteristics of social entrepreneurs in Sub Rumbai rattan overall look of the SMP and SMA by 61.54% amounting to 38.46%, on the size of the largest family of 4-5 people by 61.53%, the most business experience old is at> 10 years of 61.54%, age entrepreneurs 39.77 years on average, sex businesses by 20 male and 6 female person. Business performance in industrial use indicators rattan venture capital holdings with an average capital of Rp.113.924.115, -, the technical conditions of production are incapable category with a score of 1.64, the aspect of human resources, namely in terms of labor education Most elementary education, business profits by an average of Rp.23.124.635, -, and expansion of the marketing range are at moderate category with a score of 1.92. Keywords: Agroindustry, wicker furniture, the performance of the business.